MANAJEMEN PENDIDIKAN DALAM PENINGKATAN MUTU SEKOLAH: SEBUAH SYSTEMATIC LITERATURE REVIEW - Sulastri, Yunita; Muzari, Ahmad; Inganah, Siti (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
Improving school quality has become a strategic issue in contemporary education, requiring professional, systematic, and sustainable school management. Numerous studies have examined the role of educational management in enhancing school quality; however, existing findings remain fragmented, context-specific, and have not been comprehensively synthesized. Therefore, this study aims to systematically synthesize the literature on educational management in improving school quality. This research employed a Systematic Literature Review (SLR) method guided by the PRISMA framework. The review process involved formulating research questions, searching international and national databases indexed in Scopus, Web of Science, and Sinta, applying inclusion and exclusion criteria, and conducting quality assessment of the selected studies. A total of 49 articles were analyzed and classified into relevant, considered, and not relevant categories. The synthesis results indicate that the main themes of the literature focus on school leadership, school-based management, internal quality assurance systems, and the management of educational resources. Effective management strategies include instructional and transformational leadership, data-based strategic planning, continuous professional development for teachers, and the implementation of sustainable quality management systems. The success of these strategies is influenced by principals’ leadership capacity, teachers’ competence and motivation, school culture, availability of resources, and stakeholder support. This study concludes that improving school quality is not the result of a single policy or program but emerges from the synergy of multiple educational management functions implemented in an integrated and context-responsive manner. ABSTRAK Peningkatan mutu sekolah merupakan isu strategis dalam pendidikan kontemporer yang menuntut pengelolaan sekolah secara profesional, sistematis, dan berkelanjutan. Berbagai penelitian telah membahas peran manajemen pendidikan dalam peningkatan mutu sekolah, namun temuan-temuan tersebut masih tersebar, bersifat parsial, dan belum tersintesis secara komprehensif. Oleh karena itu, penelitian ini bertujuan untuk mensintesis secara sistematis kajian-kajian terkait manajemen pendidikan dalam peningkatan mutu sekolah. Penelitian ini menggunakan metode Systematic Literature Review (SLR) dengan mengacu pada pedoman PRISMA. Proses penelitian meliputi perumusan pertanyaan penelitian, penelusuran literatur pada basis data internasional dan nasional terindeks Scopus, WoS, dan Sinta, seleksi artikel berdasarkan kriteria inklusi dan eksklusi, serta penilaian kualitas studi. Sebanyak 49 artikel dianalisis, yang selanjutnya diklasifikasikan menjadi relevan, dipertimbangkan, dan tidak relevan. Hasil sintesis menunjukkan bahwa tema utama penelitian berpusat pada kepemimpinan sekolah, manajemen berbasis sekolah, penjaminan mutu internal, serta pengelolaan sumber daya pendidikan. Strategi manajemen yang efektif meliputi kepemimpinan instruksional dan transformasional, perencanaan berbasis data, pengembangan profesional guru, serta penerapan sistem manajemen mutu berkelanjutan. Keberhasilan implementasi strategi tersebut dipengaruhi oleh kapasitas kepemimpinan kepala sekolah, kompetensi dan motivasi guru, budaya sekolah, ketersediaan sumber daya, serta dukungan pemangku kepentingan. Penelitian ini menyimpulkan bahwa peningkatan mutu sekolah merupakan hasil sinergi berbagai fungsi manajemen pendidikan yang dijalankan secara terpadu dan adaptif terhadap konteks sekolah.